2016
DOI: 10.1002/jmv.24619
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus subtype ON1/NA1/BA9 predominates in hospitalized children with lower respiratory tract infections

Abstract: Respiratory syncytial virus (RSV) infection is the leading cause of acute respiratory tract disease in children less than 5 years old. The aim of this study was to further elucidate the molecular properties and clinical characteristics of RSV infection. The study sample included 238 patients <5 years old who were hospitalized with clinical symptoms of upper or lower respiratory tract infection (URTI or LRTI) in the Pediatric Department at the First People's Hospital of Chenzhou, South China in 2014. We subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 37 publications
2
36
0
1
Order By: Relevance
“…Nonetheless, a true comparison of RSV prevalence in different geographic areas is difficult to perform taking into account the differences in the study design and, even in our study, prevalence was wide-ranging according to the season. Bronchiolitis and pneumonia were significantly associated with RSV-positive cases among children aged < 5 years, which was consistent with previous studies that found RSV as a major cause of acute LRTI in this age group [12,[38][39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, a true comparison of RSV prevalence in different geographic areas is difficult to perform taking into account the differences in the study design and, even in our study, prevalence was wide-ranging according to the season. Bronchiolitis and pneumonia were significantly associated with RSV-positive cases among children aged < 5 years, which was consistent with previous studies that found RSV as a major cause of acute LRTI in this age group [12,[38][39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…The annual distribution of RSV during 2011-2016 in Guangzhou revealed high epidemic years for 2011, 2014, and 2015, with year 2015 as an epidemic peak. There may be a biennial high incidence pattern of RSV in Guangzhou, and surveillance over a longer period will confirm the annual distribution characteristics (Esposito et al, 2015;Xiang et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, due to N318Y, T319A, or T320S/I/P mutation, eight Guangzhou NA1 and one Guangzhou NA3 strains lost the potential N-glycosylation site at residue 318 (Figure 8). Compared to the sequences of the representative BA1 strain (BA4128/99B; Fan et al, 2017;Trento et al, 2003), all BA9 strains had K218T, L223P, and S247P substitutions. I281T and H287Y existed in most of the Guangzhou BA9 strains except GZ2012/03 and GZ/2012/15, respectively.…”
Section: Amino Acid Sequence Analysismentioning
confidence: 97%
“…RSV infection was confirmed from nasopharyngeal swabs using reverse transcription polymerase chain reaction (RT-PCR) as described previously [25]. Viral load was measured using real-time fluorescent quantitative PCR, according to a standardized protocol [26].…”
Section: Patients and Experimental Designmentioning
confidence: 99%